畢氏定理 證明 6

\begin{equation}延申\mathrm{BC}到\mathrm{D},並作直線\mathrm{DH}\perp\mathrm{AB},則\end{equation}\begin{equation}\triangle\mathrm{ABC}\sim\triangle\mathrm{DBH}\end{equation}\begin{equation}\triangle\mathrm{ABC}\sim\triangle\mathrm{AEH}\end{equation}\begin{equation}\triangle\mathrm{ABC}\sim\triangle\mathrm{DEC}\end{equation}

\begin{equation}讓\mathrm{AB}=\mathrm{c},\mathrm{BC}=\mathrm{a},\mathrm{AC}=\mathrm{b},\mathrm{CD}=\mathrm{x},\end{equation}\begin{equation}\mathrm{CE}=\mathrm{y},\mathrm{AH}=\mathrm{z}。\end{equation}

\begin{equation}\mathrm{1}. \triangle\mathrm{ABC}\sim\triangle\mathrm{DBH}\end{equation}\begin{equation}\therefore\mathrm{AB}:\mathrm{BD}=\mathrm{BC}:\mathrm{BH}\end{equation}\begin{equation}\Rightarrow\mathrm{c}:(\mathrm{a}+\mathrm{x})=\mathrm{a}:(\mathrm{c}-\mathrm{z})\end{equation}\begin{equation}\Rightarrow\mathrm{a}^2+\mathrm{ax}+\mathrm{cz}=\mathrm{c}^2\cdots\cdots(\mathrm{1})\end{equation}

\begin{equation}\mathrm{2}. \triangle\mathrm{ABC}\sim\triangle\mathrm{AEH}\end{equation}\begin{equation}\therefore\mathrm{AB}:\mathrm{AE}=\mathrm{AC}:\mathrm{AH}\end{equation}\begin{equation}\Rightarrow\mathrm{c}:(\mathrm{b}-\mathrm{y})=\mathrm{b}:\mathrm{z}\end{equation}\begin{equation}\Rightarrow\mathrm{b}^2=\mathrm{by}+\mathrm{cz}\cdots\cdots(\mathrm{2})\end{equation}

\begin{equation}\mathrm{3}. \triangle\mathrm{ABC}\sim\triangle\mathrm{DEC}\end{equation}\begin{equation}\therefore\mathrm{BC}:\mathrm{EC}=\mathrm{AC}:\mathrm{DC}\end{equation}\begin{equation}\Rightarrow\mathrm{a}:\mathrm{y}=\mathrm{b}:\mathrm{x}\end{equation}\begin{equation}\Rightarrow\mathrm{by}=\mathrm{ax}\cdots\cdots(\mathrm{3})\end{equation}

\begin{equation}將(\mathrm{3})(\mathrm{2})代入(\mathrm{1})可以即可得到\end{equation}

\begin{equation}\Rightarrow\mathrm{a}^2+\mathrm{b}^2=\mathrm{c}^2\end{equation}

Reference:

1. Elisha S. Loomis (1935): « The Pythagorean Proposition ». p. 44.

發佈留言